2010
DOI: 10.1111/j.1530-0277.2010.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Changes in MAP Kinases, Histone Modifications, and Liver Injury in Rats Acutely Treated With Ethanol

Abstract: Background-Acute ethanol is known to affect cells and organs but the underlying molecular mechanisms are poorly explored. Recent developments highlight the potential importance of mitogen activated protein kinases, MAPKs (i.e. ERK1/2, p38 and JNK1/2) signaling, and histone modifications (i.e. acetylation, methylation and phosphorylation) in the actions of ethanol in hepatocytes. We have therefore investigated significance of these molecular steps in vivo using a model in which rats were acutely administered et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 40 publications
(71 reference statements)
4
43
0
Order By: Relevance
“…This epigenetic change is associated with the increase of the histone acetyl-transferase activity and with the reduction of histone deacetylase (HDAC) 2 activity (7). In agreement with these observations, H3K9 acetylation has been observed in the liver after alcohol exposure (8). Meng et al have recently shown that epigenetic changes in hepatocytes regulate expression of certain micro-RNAs through methylation of CpG islands in their promoters (9).…”
supporting
confidence: 72%
“…This epigenetic change is associated with the increase of the histone acetyl-transferase activity and with the reduction of histone deacetylase (HDAC) 2 activity (7). In agreement with these observations, H3K9 acetylation has been observed in the liver after alcohol exposure (8). Meng et al have recently shown that epigenetic changes in hepatocytes regulate expression of certain micro-RNAs through methylation of CpG islands in their promoters (9).…”
supporting
confidence: 72%
“…We had reported previously that after an acute administration of ethanol histone H3 phosphorylation at Ser10 and Ser28 increased (Aroor et al, 2010). We have now determined the effect of different doses of ethanol on H3 phosphorylation at the 1-h time point.…”
Section: Ethanol Dose and Time Course Of Histone H3 Phosphorylationmentioning
confidence: 98%
“…We have reported that in vivo intraperitoneal acute ethanol promotes histone acetylation at Lys9 and phosphorylation at Ser10 and Ser28 (Aroor et al, 2010). We have now investigated the characteristics of histone H3 phosphorylation (Ser10, Ser28) and phosphoacetylation (K9S10) in vivo and examined their mechanistic relevance to gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…p38 MAPK is a multifunctional protein kinase and its biological role is both beneficial and harmful (Cuenda and Rousseau, 2007). The function of p38 MAPK in the liver has not been fully unveiled, but it was reported that p38 MAPK seemed to be involved in hepatotoxicity induced by some hepatotoxicants (Aroor et al, 2010;Zhang et al, 2010;Iida et al, 2009). In addition, inhibition of p38 MAPK is known to attenuate hepatic injury (Lv et al, 2012;Wang et al, 2009;Wu and Cederbaum, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although the roles of p38 MAPK in the liver have not been completely clarified, some reports indicated that p38 MAPK is involved in hepatotoxicant-induced hepatotoxicity. For example, ethanol administration elicited rapid p38 MAPK activation before hepatic necrosis occurred (Aroor et al, 2010). Likewise, activated p38 MAPK was noted after administration of lipopolysaccharide/D-galactosamine (Zhang et al, 2010) or carbon tetrachloride (Iida et al, 2009).…”
Section: Introductionmentioning
confidence: 99%